Grouping of Nouns in The Uzbek Language into Semantic Fields - Tirkashev Jasurjon Uktam ugli (International Journal Of Literature And Languages, 2026)
This article analyzes the issue of grouping nouns in the Uzbek language into semantic fields. The main objective of the research is to comprehensively group Uzbek nouns thematically and semantically, and to conduct a comparative analysis of this classification with existing semantic systems in English, Russian, and Turkish. The study utilized materials from the electronic corpus of the Uzbek language and the explanatory dictionary. As a result, 10,000 Uzbek nouns were categorized into the following six main semantic fields: Nature, Human Activity, Material Objects, Abstract Concepts, Place and Space, and Food. Each semantic field was further divided into smaller subgroups, whose proportions were statistically analyzed and represented using diagrams. The findings were compared with other languages, and commonalities and differences were examined. The research results can be applied in compiling semantic dictionaries, automatic semantic tagging, and developing multilingual ideographic dictionaries.